Technologies in Computerized Lexicography - Kruyt, J.G. (Lexikos, 1995)
Since the early eighties, computer technology has become increasingly relevant to lexicography. Computer science will probably not be the only technological discipline which may have implications for future computerized lexicography. Some developments in the fields of language technology, information technology and knowledge engineering, may support lexicographical practice and enhance the quality of the resulting dictionary. The present paper discusses how the analysis and interpretation of electronic corpus data by the lexicographer may be improved by automatic linguistic analysis, by better access to the corpus, and by a more flexible communication with the computer system. As a frame of reference, first an indication of the state of the art in computerized lexicography will be given, by a concise discussion of three projects at the Institute for Dutch Lexicology INL considered in an international context: the conversion of the Woordenboek der Nederlandsche Taal WNT (Dictionary of the Dutch Language Based on Historical Principles) to electronic form, the compilation of the Vroegmiddelnederlands Woordenboek (Dictionary of Early Middle Dutch) in a computerized lexicographer’s workbench, and the INL Taalbank (INL Language Database). Although the topic of this paper is technology, focus is on functional rather than technical aspects of computerized lexicography.